2020
DOI: 10.2298/sarh190925022v
|View full text |Cite
|
Sign up to set email alerts
|

The effect of injectable platelet-rich fibrin use in the initial treatment of chronic periodontitis

Abstract: Introduction/Objective The objective of the study was to investigate whether there are differences in therapeutic effect between initial treatments of chronic periodontitis [scaling and root planning (SRP)] alone and SRP in conjunction with injectable platelet-rich fibrin (I-PRF) application, comparing clinical parameters after three months. Methods Twenty-four patients with chronic periodontitis who had at least two sites with probing pocket depth (PPD) ≥ 5 mm on contralateral side participated in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Although there are divided opinions regarding the use of PRP in bone regeneration, some in vivo studies from other research field have shown a positive PRP effect in stimulating the healing process of bone defects [24]. Also, advanced, second generation of platelet concentrates, platelet-rich fibrin (PRF), proved to have beneficial effect in the treatment of patients with chronic periodontitis when used in combination with conservative periodontal therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are divided opinions regarding the use of PRP in bone regeneration, some in vivo studies from other research field have shown a positive PRP effect in stimulating the healing process of bone defects [24]. Also, advanced, second generation of platelet concentrates, platelet-rich fibrin (PRF), proved to have beneficial effect in the treatment of patients with chronic periodontitis when used in combination with conservative periodontal therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Control group Ten patients received a full mouth supra -and subgingival scaling and root planing only. Figure (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) .…”
Section: Patient Groupingmentioning
confidence: 99%
“…Significance of the obtained results was judged at the 5% level. The power analysis was performed according to Mila et al, for adjunctive non-surgical periodontal treatment (11) . That power analysis was conducted by G power version 3.1 statistical software, Franz Faul, Universität Kiel Germany.…”
Section: Statistical Analysis Of the Datamentioning
confidence: 99%
See 2 more Smart Citations